Riksäpplet : Arkeologiska perspektiv på ett bortglömt regalskepp. - Eriksson, Niklas (Kriterium, 2017)
"Riksäpplet deals with a shipwreck that has a neglected position in the grand narrative of the history of the Swedish navy. The story of its destiny and the missing accounts in scholarly and popular works in history says something about heritage processes within Swedish maritime archaeology. On 5 June 1676 Riksäpplet came loose and adrift from its moorings outside Dalarö Sea fortress. The hull struck a rock and sank. The loss was considered both ignominious and embarrassing and the ship's fate has been overlooked in all major history books. The rock onto which Riksäpplet sank was named 'Äpplet' after the incident, and the wreck itself has become an integrated component of the underwater seascape. As a consequence the wreckage has never enjoyed a proper 'discovery' or undergone documentation under the sensational forms that many other famous shipwrecks have, even though they have sunk in more inconvenient places. In Eriksson's study the official handling of Riksäpplet's wrecked body is compared to the more wellknown ships Kronan and Svärdet, which both sank during battle only days before. Eriksson draws on different motifs and driving forces behind the study of naval wrecks from the period from his comparison, and the differences are discussed. Riksäpplet has never achieved a prominent position with the romanticising works of history that honour the national heroes and their deeds which are associated with this era of the Swedish Empire. The first half of the book thus sets out to unpack the ideas that have led to the relative disinterest in Riksäpplet in comparison to other shipwrecks. The second half of the book sets out to analyse Riksäpplet from a specific archaeological perspective, with focus on the ship as material culture. Eriksson's departure is to explore the relatively low budget fieldwork that has been done at the wreck site. He the combines those facts with a survey of the artefacts recovered from the wreck, of which all are kept in museum archives and private collections. This, in addition to his studies of preserved written correspondence concerning the construction of the ship, has brought new insights into seventeenth-century shipbuilding and how the balance between the global political superpowers affected this trade. In this context Riksäpplet has great potential to show how military alliances are materialized through ships' architecture.